Characterization of a new type grain boundary phase in near-β titanium alloys. (1st March 2020) - Zhang, Hongling; Zhang, Xiaoyong; Zhu, Zhishou; Li, Chao; Zhou, Kechao
Abstract: After 920 °C/120 min → WQ + 780 °C/300 min → air fast cooling heat treatment, a banded ω' phase distributing at interfaces between the β matrix and grain boundary α phase was discovered in a Ti-4.5Al-6.5Mo-2Cr-2.5Nb-2Zr-1Sn (wt%) alloy. The ω' phase shows a P6/mmm hexagonal close packed lattice crystal structure and its lattice parameters are a = 0.399 nm, c = 0.282 nm. The orientation relationship between ω' and adjacent β phase are (110)β1 //(1 1 ¯ 00)ω', (111)β1 //(0001)ω', and (112)β1 //(11 2 ¯ 0)ω' . The atom migration path during the β → ω' phase is (121)β plane collapse along the <010>β direction. Graphical abstract: Image, graphical abstract